2022
DOI: 10.24259/fs.v6i1.13991
|View full text |Cite
|
Sign up to set email alerts
|

Cacao-based Agroforestry in Conservation Forest Area: Farmer Participation, Main Commodities and Its Contribution to the Local Production and Economy

Abstract: Cacao-based agroforestry systems have been developed in the conservation forest area of Wan Abdul Rachman Grand Forest Park (WAR GFP). Previously, the forest areas were occupied by surrounding needy communities, causing land-use conflict and forest degradation. To resolve these problems, the conservation forest manager developed a conservation partnership program, giving farmers legal access to establish cacao agroforestry systems while improving forest conditions. This research aimed to study the farmers’ par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
(56 reference statements)
0
2
0
1
Order By: Relevance
“…Agroforestry diversifies the land's production [11] and has benefits for environmental parameters, including climate change mitigation and adaptation, biodiversity enhancement, and soil and water preservation [12,13], with implications for farmer resilience, specifically in marginal areas [14]. Murniati et al reported that agroforestry contributed to 75.63% of total farmers' household income [15]. In semi-arid areas, the net productivity of any agroforestry system depends on how its components interact over time and space for the same resource (water, nutrients, light).…”
Section: Introductionmentioning
confidence: 99%
“…Agroforestry diversifies the land's production [11] and has benefits for environmental parameters, including climate change mitigation and adaptation, biodiversity enhancement, and soil and water preservation [12,13], with implications for farmer resilience, specifically in marginal areas [14]. Murniati et al reported that agroforestry contributed to 75.63% of total farmers' household income [15]. In semi-arid areas, the net productivity of any agroforestry system depends on how its components interact over time and space for the same resource (water, nutrients, light).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of external strategic factors is carried out by identifying opportunities and threats from various aspects of the external environment that affect the development of cocoa commodities [11,12] After identifying the external strategic factors for the development of cocoa commodities, an EFAS (External Factor Analysis Summary) table is created. Based on the calculation results for each rating, the weighting obtained for each external factor rating value is presented in Table 4.…”
Section: External Factor Analysismentioning
confidence: 99%
“…Bentuk aktivitas mereka dalam kawasan tahura adalah menggarap lahan dengan bercocok tanam yang telah dilakukan sejak dahulu dan turun temurun hingga saat ini. Hal tersebut memicu timbulnya konflik penggunaan lahan dan degradasi hutan (Murniati et al, 2022a). Oleh karena itu, diperlukan pendekatan melalui penerapan agroforestry dalam penggunaan lahan yang senantiasa mempertimbangkan aspek ekologi, sosial, dan ekonomi (Hartoyo et al, 2019).…”
Section: Pendahuluanunclassified